Variabilidade comportamental e a aquisição de respostas com baixa probabilidade inicial de ocorrência - Caldeira, Karine Marques (2009)
Behavioral variability is an operant dimension of behavior and, as like other dimensions, can be directly reinforced. Researches with animals have demonstrated that a history involving reinforcement of variability helps in the acquisition of new responses. The goal of the present work was to verify if direct reinforcement of variability can help human participants to acquire a response with low initial probability of occurrence and verify if conditions which involve different response cost have influence on produced variability. Eighteen adults were participants and they had to press two keys (on two keyboards, placed side by side) to produce a sequence of four responses. Six groups were made and they could vary the distance of the keyboards (distant or close), the conditions to which the participants were exposed to, and the order of exposition to the experimental conditions. The Var condition involved two contingencies operating concurrently: 1) completing sequences that reached the variability criterion established (on a schedule that consider the weighted relative frequency of a response called RDF), and 2) completing a specific target sequence on a VR2 schedule. The Aco condition also involved two contingencies operating concurrently: 1) completing sequences without being required to vary, but with availability of reinforcement according to the availability of reinforcement obtained in Var, and 2) completing a specific target sequence on a VR2 schedule. Control condition involved only one condition: completing a specific target sequence on a VR2 schedule. The results were analyzed according to the distribution of the responses within all the possible sequences and the evenness of this distribution, and also in relation to the U value. The results point that the contingency that required variability was effective in producing higher variability of responses compared to the variability observed in baseline. Nevertheless, the majority of participants that learned to complete the target sequence were from the groups of control condition. Furthermore, the different distances between the keyboards did not produce differences in response variability among the groups. The results presented on this work do not corroborate the results found on the literature in relation to the participants that were not exposed to direct reinforcement of variability learn the target sequence more frequently